Qiyās and Its Relevance to Addressing Contemporary Islamic Legal Issues - Braham Maya Baratullah; Mohammed Hafiz Ali Wafa; Hasman Zhafiri Muhammad; Khamid Abinawa Al Barki (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2026)
The rapid development and transformation of society have generated various contemporary legal issues that are not explicitly addressed in the Qur’an and Sunnah. This condition requires a method of ijtihād capable of responding adaptively to emerging legal issues without neglecting the fundamental principles of Islamic law. Qiyās is one of the methods of ijtihād in Uṣūl al-Fiqh that employs analogical reasoning to determine the legal ruling of a new case (far‘) on the basis of an existing case (aṣl) whose ruling has been established by Islamic law, due to the presence of a common legal cause (‘illah) between the two. This study aims to examine the concept of qiyās in Uṣūl al-Fiqh and analyze its relevance in addressing contemporary Islamic legal issues. This research employs a library research method with a normative-qualitative approach. The data are derived from classical and contemporary Uṣūl al-Fiqh literature and analyzed using a descriptive-analytical method. The findings indicate that qiyās remains relevant as a method of ijtihād for addressing contemporary Islamic legal issues, particularly when a particular issue has no direct legal ruling in the textual sources (nuṣūṣ). Nevertheless, its application must comply with the principles and essential elements of qiyās and take into consideration the objectives of Islamic law (maqāṣid al-sharī‘ah). Therefore, qiyās can serve as an important instrument for maintaining the flexibility, relevance, and continuity of Islamic law in responding to the dynamics of modern life.